Impact of High-Sensitivity Troponin I Testing with Sex-Specific Cutoffs on the Diagnosis of Acute Myocardial Infarction. (6th January 2020) - Trambas, Christina; Pickering, John W; Than, Martin; Bain, Chris; Nie, Lucy; Paul, Eldho; Dart, Anthony; Broughton, Arch; Schneider, Hans Gerhard
Abstract: BACKGROUND: High-sensitivity cardiac troponin I (hs-cTnI) assays show sex-dependent differences in the 99th percentile of healthy populations, with concentrations in women approximately 50% lower. The adoption of sex-specific cutoffs seems appropriate, although it is not yet clear what effect these will have on acute myocardial infarction (AMI) diagnosis and management. METHODS: We conducted a retrospective pre- and postchangeover analysis of troponin I testing in the 6 months before and after moving from the contemporary Abbott Architect TnI assay (cTnI) to hs-cTnI at 2 tertiary centers in Australia and New Zealand. The cTnI cutoff was 30 ng/L for both sexes, whereas a female-specific cutoff of 16 ng/L was adopted upon changeover to hsTnI. RESULTS: Changeover from the cTnI assay to the hs-cTnI assay increased the number of female patients with increased troponin I concentrations at both sites (from 29.7% to 34.9% and from 22.4% to 30.8%; P < 0.001). There was no statistically significant change in the number of men with increased concentrations in the same time period ( P = 0.09). The increased percentage of women with increased troponin I was not associated with an increase in the number of women with AMI diagnoses at either center. Angiographic data available from 1 center showed no change in the percentage of angiograms performed in women. CONCLUSIONS: Although increasing the proportion of women with increased troponin I, adopting sex-specific cutoffs with the hs-cTnI assay did not lead to an increase in AMI diagnoses in females, or in the number of women undergoing angiography.